LMTK1, a Novel Modulator of Endosomal Trafficking in Neurons - Hisanaga, Shin-ichi; Wei, Ran; Huo, Anni; Tomomura, Mineko (Frontiers in Molecular Neuroscience, 2020)
Neurons extend long processes known as axons and dendrites, through which they communicate with each other. The neuronal circuits formed by the axons and dendrites are the structural basis of higher brain functions. The formation and maintenance of these processes are essential for normal brain activities. Membrane components, both lipids and proteins, that are required for process formation are supplied by vesicle transport. Intracellular membrane trafficking is regulated by a family of Rab small GTPases. A group of Rabs regulating endosomal trafficking has been studied mainly in nonpolarized culture cell lines, and little is known about their regulation in polarized neurons with long processes. As shown in our recent study, lemur tail (former tyrosine) kinase 1 (LMTK1), an as yet uncharacterized Ser/Thr kinase associated with Rab11-positive recycling endosomes, modulates the formation of axons, dendrites and spines in cultured primary neurons. LMTK1 knockdown or knockout or the expression of a kinase-negative mutant stimulates the transport of endosomal vesicles in neurons, leading to the overgrowth of axons, dendrites and spines. More recently, we found that LMTK1 regulates TBC1D9B Rab11 GAP and proposed the Cdk5/p35-LMTK1-TBC1D9B-Rab11 pathway as a signaling cascade that regulates endosomal trafficking. Here, we summarize the biochemical, cell biological and physiological properties of LMTK1.